An examination into the effects of tocotrienols (TheraPrimE® rice) on cognitive abilities and sleep in healthy adults: a randomised, double-blind, placebo-controlled trial - Lopresti, Adrian L.; Smith, Stephen J.; Ding, Lixin; Li, Yanmei; Zhang, Peinan (Frontiers in Nutrition, 2025)
Background/objectivesTocotrienols are a form of vitamin E that may have neuroprotective effects. However, there have been no studies examining its effects on cognitive function when delivered as a stand-alone intervention. The purpose of this two-arm, 12-week, randomised, double-blind, placebo-controlled trial was to examine the effects of supplementation with tocotrienols derived from rice bran (TheraPrimE® rice) on memory and sleep in adults with subjective memory complaints.MethodsNinety-one adults aged 40–80 were supplemented with a placebo or 100 mg of tocotrienols daily. Outcome measures included the Test of Memory and Learning (version 2), and self-report questionnaires assessing executive function and sleep quality. Moreover, changes in blood markers associated with inflammation, oxidative stress, and neurotropic activity were examined.ResultsCompared to the placebo, tocotrienol supplementation was associated with greater improvements in general memory (p = 0.045, 95% CI: 0.34, 32.21). Memory changes were primarily due to improvements in non-verbal memory (p = 0.039, 95% CI: 0.68, 26.63). However, there were no group differences in changes in verbal memory. Moreover, there were no group differences in changes in self-reported executive function, although there were greater improvements in sleep disturbance in the tocotrienols group (p = 0.015, 95% CI: −4.80, −0.55). An examination of blood markers revealed a statistically significant larger increase in Tumour Necrosis Factor-α in the placebo group (p = 0.043) and a larger increase in C-reactive protein (p = 0.039) in the tocotrienols group. Tocotrienols were not associated with any serious adverse reactions.ConclusionThis is the first controlled study demonstrating the cognitive-enhancing and sleep-promoting effects of stand-alone supplementation with tocotrienols. However, future research is required to substantiate this study’s results and examine the potential mechanisms of action.Clinical trial registrationhttps://www.anzctr.org.au/ACTRN12624000351516.aspx, Identifier ACTRN12624000351516.